Widespread somatosensory sensitivity in naturally occurring canine model of osteoarthritis. Issue 6 (June 2016) - Knazovicky, David; Helgeson, Erika S.; Case, Beth; Gruen, Margaret E.; Maixner, William; Lascelles, B. Duncan X.
Abstract : Abstract: Osteoarthritis (OA)-associated pain is a leading cause of disability. Central sensitization (CS), as a result of OA, is recognized as an important facet of human patients' chronic pain and has been measured in people using quantitative sensory testing (QST) testing. The spontaneous canine OA model has been suggested as a good translational model, but CS has not been explored in this model. In this study, QST was performed on dogs with and without spontaneous hip or stifle OA to determine whether OA is associated with CS in this model. Mechanical (von Frey and blunt pressure) and thermal (hot and cold) sensory thresholds obtained in dogs with chronic OA-associated pain (n = 31) were compared with those of normal dogs (n = 23). Dogs were phenotyped and joint-pain scored, and testing was performed at the OA-affected joint, cranial tibial muscle, and dorsal metatarsal region. QST summary data were evaluated using mixed-effect models to understand the influence of OA status and covariates, and dogs with OA and control dogs were compared. The presence of OA was strongly associated with hyperalgesia across all QST modalities at the index joint, cranial tibial muscle, and metatarsal site. Mechanical QST scores were significantly moderately negatively correlated with total joint-pain scores. The spontaneous canine OA model is associated with somatosensory sensitivity, likely indicative of CS. These data further validate the canine spontaneous OA model as an appropriate model of the human OA pain condition. Abstract : Supplemental Digital Content is Available in the Text.The spontaneous osteoarthritis model in dogs shows evidence of central sensitization as evidenced by multimodality quantitative sensory threshold testing.